2018
DOI: 10.1007/978-1-4939-7799-4_6
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Adipose Tissue Scaffolds for Soft Tissue Regeneration and Adipose-Derived Stem/Stromal Cell Delivery

Abstract: Surgically discarded adipose tissue is not only an abundant source of multipotent adipose-derived stem/stromal cells (ASCs) but can also be decellularized to obtain a biomimetic microenvironment for tissue engineering applications. The decellularization methods involve processing excised fat through a series of chemical, mechanical, and enzymatic treatment stages designed to extract cells, cellular components, and lipid from the tissues. This process yields a complex 3D bioscaffold enriched in collagens that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Over the next decade, the Flynn laboratory went on to demonstrate that DAT could be prepared in multiple formulations (hydrogel, microcarrier bead, powder) to regenerate soft tissue in vivo. 90 In parallel, independent studies from multiple teams have demonstrated that DAT is biocompatible with fibroblasts and ASCs, can serve as a platform for the release of paracrine growth factors in MPS constructs, and supports the in vitro and in vivo adipogenic and osteogenic differentiation of ASCs (reviewed in Mohiuddin et al 91 ).…”
Section: Ecm: Biological and Synthetic Alternatives To Matrigelmentioning
confidence: 98%
“…Over the next decade, the Flynn laboratory went on to demonstrate that DAT could be prepared in multiple formulations (hydrogel, microcarrier bead, powder) to regenerate soft tissue in vivo. 90 In parallel, independent studies from multiple teams have demonstrated that DAT is biocompatible with fibroblasts and ASCs, can serve as a platform for the release of paracrine growth factors in MPS constructs, and supports the in vitro and in vivo adipogenic and osteogenic differentiation of ASCs (reviewed in Mohiuddin et al 91 ).…”
Section: Ecm: Biological and Synthetic Alternatives To Matrigelmentioning
confidence: 98%
“…Upregulation of laminin expression during the early stage has been found to initially increase the expression of type I collagen, but later to decrease its expression significantly ( Mariman and Wang, 2010 ), followed by the alteration of ECM components from fibrillary collagen types I, III, and V to basement membrane types IV and VI( Mor-Yossef Moldovan et al, 2019 ). The components and proteins secreted by ASCs and preadipocytes optimized ECM remodeling and produced critical biochemical and physical signals ( Morissette Martin et al, 2018 ). Exosomes derived from human adipose mesenchymal stem cells (hASCs-Exos) can be recruited to soft-tissue wound areas of a mouse skin incision model, increasing the production of collagen types I and III during early stages ( Hu et al, 2016 ).…”
Section: Factors Affecting Extracellular Matrix Remodelingmentioning
confidence: 99%
“…The methodology for decellularizing adipose tissue was pioneered by Flynn and colleagues [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] and has since been confirmed by multiple independent laboratories [ 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. These methods combine biological (enzyme digestion), chemical, and physical processing steps to achieve the uniform and consistent manufacture of protein scaffolds depleted of contaminating genomic DNA and lipids.…”
Section: Extracellular Matrix (Ecm) From Decellularized Adipose Timentioning
confidence: 99%